PENGARUH PENERAPAN MANAJEMEN TALENTA TERHADAP KINERJA KARYAWAN PT. JAPFA COMFEED INDONESIA TBK. UNIT MARGOMULYO - Fithratun Nisak; Setya Prihatiningtyas (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2021)
Every company wants its business to continue to growth, develop and improve, along with changing times and technological developments. To be able to continue to growth and develop in the midst of increasingly rapid changes in the external. Environment, a company must focus on changing its internal factors, namely finding, attracting and retaining the best people in the company. Only the best people, in sufficient numbers, in the right position and with optimal utilization, can encourage the company to continue to growth. To get the best people, a company uses a talent management system that functions to find out the performance of the best people. The purpose of this study is to determine whether there is an influence of talent management on the performance of employees of PT. Japfa Comfeed Indonesia Tbk. Margomulyo Unit. This research is a quantitative research using the positivism paradigm based on the existing theory, namely the theory regarding the influence of talent management on employee performance. The results of this study are that there is an influence between talent management and the performance of employees of PT. Japfa Comfees Indonesia Tbk. The Margomulyo unit of t-count value of 6.052 is greater than t-table of 1.982, so Ho is rejected and Ha is accepted.